Recommendations for cerebrospinal fluid analysis - Hepnar, D; Adam, P; Žáková, H; Krušina, M; Kalvach, P; Kasík, J; Karpowicz, I; Nasler, J; Bechyně, K; Fiala, T; Mamiňák, M; Malíková, I; et al. (Folia microbiologica, 2019)
Diseases of the central nervous system (CNS) mean for the human organism a potentially dangerous situation. An investigation of cerebrospinal fluid (CSF) provides important information about a character of CNS impairment in the decision-making diagnostic and therapeutic algorithm. The authors present a brief overview of available cerebrospinal fluid assays, shortened indication criteria, a recommended algorithm of CSF assessment in different suspected diseases, and a view of the external quality system. The whole portfolio of obtainable CSF methodology is further subdivided according to the adequate choice into the first and inevitable basic routine panel, and following complicated analyses of highly specialized character. The basic panel is considered for standard laboratories, the complete specialized assessment should be provided by a super-consulting laboratory.
Keywords: proteiny v mozkomíšním moku; Cerebrospinal Fluid Proteins; Algorithms; Clinical Laboratory Techniques; klinické laboratorní techniky; makrofágy; Cytological Techniques; cytologické techniky; lidé; Cerebrospinal Fluid; Macrophages; Practice Guidelines as Topic; algoritmy; Humans; směrnice pro lékařskou praxi jako téma; mozkomíšní mok